From the Bottom Up : How Small Power Producers and Mini-Grids Can Deliver Electrification and Renewable Energy in Africa - Tenenbaum, Bernard; Greacen, Chris; Siyambalapitiya, Tilak; Knuckles, James (Washington, DC: World Bank, 2014)
Most Sub-Saharan African countries try to promote rural electrification through both centralized and decentralized approaches. This guide focuses on the decentralized approach, providing practical guidance on how small power producers and mini-grid operators can deliver both electrification and renewable energy in rural areas. It describes four basic types of on- and off-grid small power producers, as well as several hybrid combinations that are emerging in Africa and elsewhere. The guide highlights the ground-level regulatory and policy questions that must be answered by electricity regulators, rural energy agencies, and ministries to promote commercially sustainable investments by private operators and community organizations.